2022
DOI: 10.1079/cabionehealth.2022.0008
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Q-fever in domestic ruminants and humans in Africa. A systematic review

Abstract: Q-fever is a zoonotic infectious disease caused by the gram-negative, intracellular, spore-forming bacterium Coxiella burnetii . Infected ruminants (cattle, sheep, and goats) are the reservoirs of the pathogen and thus an important source of infection in humans. This systematic review aims to consolidate the knowledge and awareness of Q-fever in Africa and identify future research opportunities and possible interventions in low-resource settings. We review information on Q-fever epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 103 publications
3
3
1
Order By: Relevance
“…Seroprevalence of coxiellosis was significantly higher in goats than in sheep in this meta-analysis. The findings of this study are in-line with the findings of other regional meta-analyses (Ahmadinezhad et al, 2022;Bwatota et al, 2022;Nokhodian et al, 2017). There is no con- breaks (Anastácio et al, 2022;Bauer et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Seroprevalence of coxiellosis was significantly higher in goats than in sheep in this meta-analysis. The findings of this study are in-line with the findings of other regional meta-analyses (Ahmadinezhad et al, 2022;Bwatota et al, 2022;Nokhodian et al, 2017). There is no con- breaks (Anastácio et al, 2022;Bauer et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The estimated prevalence of this study is similar to the findings of another meta‐analysis, which is based on data from the Eastern Mediterranean region (parts of Africa and the Middle East), which reported a high prevalence of coxiellosis in sheep (25.1%) and goats (28.1%) (Ahmadinezhad et al., 2022). The pooled estimates found in this study were higher than the reported pooled prevalence (sheep 13.00%, goats 21.00%) of another meta‐analysis that was conducted in Africa between 2000 and 2022 (Bwatota et al., 2022). The discrepancies are possibly due to differences in article inclusion criteria, search repositories and publication range limitation.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Moreover, a significantly elevated seroprevalence rate of (73.17%) was recorded when cattle shared an environment with small ruminants, this finding is in accordance with (Menadi et al, 2020). This might linked to the increased susceptibility of hosts, especially goats and sheep where they act as the most susceptible farm animals and at high risk, serving as potential carriers capable of transmitting the disease to other ruminants (Bwatota et al, 2022). Significantly, age and breed played crucial roles in impacting C. burnetii seroprevalence, particularly older cattle aged above 4 years, which exhibited a higher seroprevalence rate of (67.44%) followed by (40.63%) in the 2-4 years age category; meanwhile, the lowest seroprevalence rate of (20%) was observed in cattle under 2 years.…”
Section: Resultssupporting
confidence: 66%